Socialization Of Food Packaging Labeling In Msme Food Products In Pagelaran Village: Sosialisasi Pelabelan Kemasan Pangan Di Umkm Produk Pangan Desa Pagelaran - Amelia, Julfi Restu; Utami, Annisa Retno; Ratnasari, Kania (Universitas Lancang Kuning, 2025)
Pagelaran Village, Ciomas, Bogor, has several food product MSMEs that do not yet have packaging labels. Packaging labeling is an important thing to consider because it can influence consumer decisions in purchasing food products, so socialization related to this is important to do. The PKM activities carried out aim to socialize packaging labeling in several food product MSMEs and increase respondents' knowledge regarding food labels. The socialization method is carried out through lectures and demonstrations. The level of success of the socialization is measured using the pre-test and post-test methods using Google Forms. The results of the success measurement show that there is an increase in the knowledge of socialization participants regarding food packaging labeling and the components contained therein. These results also show that there is an increase in participants' knowledge regarding things that are not allowed to be included in food labels